Pediatric reference intervals for plasma free and total metanephrines established with a parametric approach: Relevance to the diagnosis of neuroblastoma. Issue 4 (16th January 2015) - Franscini, Laura Crosazzo; Vazquez‐Montes, Maria; Buclin, Thierry; Perera, Rafael; Dunand, Marielle; Grouzmann, Eric; Beck‐Popovic, Maja
<x xml:space="preserve">Abstract</x> Background Urine catecholamines, vanillylmandelic, and homovanillic acid are recognized biomarkers for the diagnosis and follow‐up of neuroblastoma. Plasma free (f) and total (t) normetanephrine (NMN), metanephrine (MN) and methoxytyramine (MT) could represent a convenient alternative to those urine markers. The primary objective of this study was to establish pediatric centile charts for plasma metanephrines. Secondarily, we explored their diagnostic performance in 10 patients with neuroblastoma. Procedure We recruited 191 children (69 females) free of neuroendocrine disease to establish reference intervals for plasma metanephrines, reported as centile curves for a given age and sex based on a parametric method using fractional polynomials models. Urine markers and plasma metanephrines were measured in 10 children with neuroblastoma at diagnosis. Plasma total metanephrines were measured by HPLC with coulometric detection and plasma free metanephrines by tandem LC‐MS. Results We observed a significant age‐dependence for tNMN, fNMN, and fMN, and a gender and age‐dependence for tMN, fNMN, and fMN. Free MT was below the lower limit of quantification in 94% of the children. All patients with neuroblastoma at diagnosis were above the 97.5th percentile for tMT, tNMN, fNMN, and fMT, whereas their fMN and tMN were mostly within the normal range. As expected, urine assays were inconstantly predictive of the disease. Conclusions A continuous model incorporating all data for a given analyte represents an appealing alternative to arbitrary partitioning of reference intervals across age categories. Plasma metanephrines are promising biomarkers for neuroblastoma, and their performances need to be confirmed in a prospective study on a large cohort of patients. Pediatr Blood Cancer 2015;62:587–593. © 2015 Wiley Periodicals, Inc.